Sosialisasi dan Penanaman Nilai-Nilai Tasawuf Dalam Pembinaan Akhlak Remaja Di Yayasan Bonavida Singgeura Milir Indramayu - Sairin; Jubaedah, Idah; Sobirin (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This Community Service Program (PKM) aims to enhance the moral character of adolescents through the socialization and internalization of Sufi values at Yayasan Bonavida Singgeura Milir, Kampung Cipendang Bunder, Indramayu. The program was motivated by the increasing moral crisis among youth, including violence, drug abuse, and declining manners. The Sufi approach was chosen due to its relevance in shaping character through soul purification (tazkiyatun nafs) and values such as sincerity, patience, and trust in God. The implementation methods included educational seminars and interactive discussions involving 30 junior and senior high school students and 5 foundation staff. The results showed a 40% increase in participants’ understanding of Sufi moral values (based on questionnaires) and enthusiasm for applying them in daily life. The academic output, this scientific article, is intended for publication in a Sinta 5 accredited journal, contributing to the development of knowledge and character-building practices.